Análisis de la reparación dispuesta en el dictamen emitido por el comité de derechos humanos en el caso Isaías Dassum contra ecuador en cuanto a la incautación de bienes. - Álvarez León, Juan Carlos (2021)
This case analysis examines the legal implications, scope, and effects of the reparation recommended by the Human Rights Committee in the views adopted on the communication submitted by Messrs. William and Roberto Isaías Dassum against the Ecuadorian State. Before, the basic concepts on international responsibility of the State and reparation are exposed, and the legal value of the decisions of the non-jurisdictional conventional organizations is analyzed, as well as the obligatory nature or not of their recommendations. The examination of the specific case includes a description of the international contentious procedure and the content of the decision adopted by the Committee, in order to achieve clarity on the decision and its factual and legal consequences. The document exposes the legal nature of the reparation and the way of interpreting it, to finally recommend the suitable legal mechanism and expose the possible difficulties that could arise in domestic law, to make the reparation available